Living in Rural Areas and Receiving Cancer Treatment Away From Home: A Qualitative Study Foregrounding Temporality - Halldóra Egilsdóttir; Helga Jónsdóttir; Marianne Elisabeth Klinke (SAGE Publishing, 2022)
We used explorative interviews to gauge (inter)personal, physiological, and emotional challenges of seven rural cancer patients who traveled long distances to cancer treatment centers. After a thematic analysis, we foregrounded experiences of temporality by using a phenomenologically inspired approach. The analysis resulted in three themes: (a) An epiphany of "what really matters in life"-time gains new meaning, (b) Feeling out of sync with others and own body-striving for coherence and simultaneity, and (c) Being torn between benefits of home and treatments site-time and distance as a tangible aspect of traveling and being away. Under these themes, 13 meaning units were generated, which reflected changes in temporality. During treatment, life primarily revolved around repeating circles of travel arrangements, staying on top of treatment schedule, and synchronizing a home life with a life away from home. Nurses should provide comprehensive care to enhance stability in cancer patients' temporal experiences.